The Effects of Vitamins E and D Supplementation on Erythrocyte Superoxide Dismutase and Catalase in Atopic Dermatitis - MH Javanbakht; SA Keshavarz; A Mirshafiey; M Djalali; F Siassi; MR Eshraghian; AR Firooz; H Seirafi; AH Ehsani; M Chamari (Tehran University of Medical Sciences, 2010)
"nBackground: Atopic dermatitis is a public health problem worldwide. Increment of reactive oxygen species (ROS) production may be one of the contributing factors of tissue damage in atopic dermatitis. The present study was designed to determine the effect of vitamins E and/or D on erythrocyte superoxide dismutase and catalase activities in patients with atopic dermatitis. "nMethods: In a randomized, double blind, placebo controlled clinical trial 45 atopic dermatitis patients were divided into four groups. Each group received one of the following supplements for 60 days: group A (n=11) vitamins E and D placebos; group B (n= 12) 1600 international unit (IU) vitamin D3 plus vitamin E placebo; group C (n=11) 600 IU synthetic all-rac-α tocopherol plus vitamin D placebo; group D (n=11) 1600 IU vitamin D3 plus 600 IU synthetic all-rac-α tocopherol. Erythrocyte superoxide dismutase (SOD) and catalase activities, serum 25 (OH) D, plasma α-tocopherol were determined. The data were analyzed by analysis of variance (ANOVA) and paired t-test. "nResults: After 60 days vitamin D and E supplementation, erythrocyte SOD activities increased in groups B, C and D (P= 0.002, P= 0.016 and P= 0.015, respectively). Erythrocyte catalase activities increased in groups B and D (P= 0.026 and P= 0.004, respectively). The increment of erythrocyte catalase activity was not significant in group C. There was a positive significant correlation between SOD activity and serum 25 (OH) D (r= 0.378, P= 0.01)."nConclusions: It is concluded that vitamin D is as potent as vitamin E in increasing the activities of erythrocyte SOD and catalase in atopic dermatitis patients.